Elastic-plastic fracture analysis of anisotropy effect on AA2050-T84 alloy at different temperatures: A Numerical Study (Fracture and Structural Integrity, 2021)
The third generation Al-Li alloy AA2050-T84 is widely used in aircraft applications due to its lightweight and significant mechanical properties. The anisotropic variations of tensile and compression properties of this alloy at various temperatures are substantial. In this work, the variations of the J-integral, CTOD, and Plastic Zone Size (PZS) due to anisotropy of a 4-inch thick AA2050-T84 plate at ambient and cryogenic temperatures were studied numerically by using Compact Tension (C(T)) specimen. The material anisotropy resulted in fracture and constraint parameter variation for Mode-I constant load. Numerical results indicated a decrease in crack driving forces and a constraint parameter with the decrease in temperature at the plate surface and central location. Plate surface locations appear to be isotropic for both temperatures under elastic-plastic fracture analyses as crack driving forces were almost identical. The temperature effect is more on constraint as the normalized PZS values at ambient temperature have been twice that of cryogenic temperature. The isotropic behavior of a plate under sub-zero temperature makes the plate suitable for cryogenic temperature applications.
Keywords: AA2050-T84 Al-Li alloy; J-integral; CTOD; Constraint parameter; Plastic Zone Size